Lo sublime opresor o lo sublime como ideología - Mahecha, Iván (CUADERNOS KÓRE, 2011)
The oppressive sublime or the sublime as ideology. This paper shows the ideological use underlying to the interpretations of the sublime, which would be a ’perverse use of the aesthetic’. It critically assesses the interpretations made by Kant and Lyotard to the concept of the sublime, in order to establish the possible oppressive uses they entail. Once unveiled the oppression that underlies to the traditional use of the concept sublime, this oppression is linked to the concept of hegemony. It concludes by identifying a possible relationship between the link oppression-hegemony with the notion of Ideology, and the relationship oppression-hegemony-ideology that underlies the interpretations of the sublime.